2007
DOI: 10.2500/ajr.2007.21.3097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Antifibrinolytics in Endoscopic Sinus Surgery: A Pilot Randomized Controlled Trial

Abstract: Topical application of TA is effective in achieving hemostasis and improving the surgical field. In contrast to EACA, TA is a valuable tool in ESS that merits additional evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 38 publications
3
69
0
3
Order By: Relevance
“…The surgical field quality was reported on two different scoring system, the Boezaart system (37) by Alimian et al (32) , Athanasiadis et al (33) and Jabalameli et al (35) , and the Wormald system (33) by…”
Section: Surgical Field Qualitymentioning
confidence: 99%
“…The surgical field quality was reported on two different scoring system, the Boezaart system (37) by Alimian et al (32) , Athanasiadis et al (33) and Jabalameli et al (35) , and the Wormald system (33) by…”
Section: Surgical Field Qualitymentioning
confidence: 99%
“…They include porcine gelatin (Surgiflo Ò ; Johnson & Johnson, Somerville, NJ) [6], topical antifibrinolytics (Amicar Ò ; Xanodyne Pharmacal, Inc., Florence, KY) [7], hyaluronic acid [3,8], oxidized regenerated cellulose (Surgicel Ò ; Xanodyne Pharmacal, Inc., Florence, KY) [9], and polyethylene glycol (Nasopore Ò ; Stryker Canada, Hamilton, Ontario, Canada) [10]. Several studies showed effectiveness of these materials in eliminating a painful removal procedure and preventing postoperative bleeding and adhesion [3,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Topical administration results in a ten-fold less plasma concentration of TXA when compared to intravenous administration [8,64], with a potential reduction in adverse effects. Although topical TXA has been studied in cardiothoracic [65−68], orthopedic [64, 69−72], otorhinolaryngologic [73,74] and orthognathic [75−77] surgeries, high-quality trials are lacking.…”
Section: Topical Usementioning
confidence: 99%